2021
DOI: 10.1155/2021/4990941
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation and Diagnostic Value of Serum Cys-C, RBP4, and NGAL with the Condition of Patients with Traumatic Acute Kidney Injury

Abstract: There is a lack of targeted biomarkers that can diagnose Acute Kidney Injury (AKI) early and accurately, which leads to deterioration of renal function and even death in patients who do not receive timely and effective treatment. In recent years, an increasing number of studies have shown that AKI-related markers such as cystatin C (Cys-C) and retinol-binding protein (RBP) can be used for early diagnosis of AKI to a certain extent. A total of 262 subjects were included in this study, of which 132 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Many studies have shown that serum NGAL can predict acute kidney injury. [ 36 , 37 ] NGAL protects against kidney damage and prevents renal fibrosis [ 38 ]. NGAL can be used for both stratification of AKI and as a guide for the next step in treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that serum NGAL can predict acute kidney injury. [ 36 , 37 ] NGAL protects against kidney damage and prevents renal fibrosis [ 38 ]. NGAL can be used for both stratification of AKI and as a guide for the next step in treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that CysC can be used for early prediction of AKI (Hou et al, 2021;Ye et al, 2021;Galic et al, 2022), including in patients with HBV-ACLF complicated by AKI (Wan et al, 2013). A recent study demonstrated that HMGB1 is a potential preprocedural predictor of contrast-induced AKI after percutaneous coronary artery intervention (Mo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%